2022
DOI: 10.1038/s41420-022-00872-2
|View full text |Cite
|
Sign up to set email alerts
|

YTHDF1 alleviates sepsis by upregulating WWP1 to induce NLRP3 ubiquitination and inhibit caspase-1-dependent pyroptosis

Abstract: Pyroptosis is inflammation-associated caspase-1-dependent programmed cell death, which confers a crucial role in sepsis. The present study intends to investigate the regulatory network and function of the microarray-predicted YTHDF1 in caspase-1-dependent pyroptosis of sepsis. Peripheral blood of patients with sepsis was collected to determine WWP1 and YTHDF1 expression. An in vitro sepsis cell model was induced in RAW264.7 cells using lipopolysaccharide (LPS) and ATP and an in vivo septic mouse model by cecal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Moreover, Enteropathogenic Escherichia coli uses NleA to inhibit NLRP3 inflammasome activation by ubiquitination of NLRP3 (Yen et al, 2015), and LPS along with ATP stimulation initiated K63-and K48-linked polyubiquitination of NLRP3 (J. Tang et al, 2020;Zhang et al, 2022). In the present study, we found that increased K48-linked polyubiquitination of NLRP3 was observed upon downregulating USP9X.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Moreover, Enteropathogenic Escherichia coli uses NleA to inhibit NLRP3 inflammasome activation by ubiquitination of NLRP3 (Yen et al, 2015), and LPS along with ATP stimulation initiated K63-and K48-linked polyubiquitination of NLRP3 (J. Tang et al, 2020;Zhang et al, 2022). In the present study, we found that increased K48-linked polyubiquitination of NLRP3 was observed upon downregulating USP9X.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies showed that hepatitis C virus infection inhibited K63‐linked polyubiquitination of NLRP3 (Ramachandran et al, 2021) and Giardia infection‐induced NLRP3 inflammasome activation was involved in its K63 deubiquitination (L. Liu et al, 2021). Moreover, Enteropathogenic Escherichia coli uses NleA to inhibit NLRP3 inflammasome activation by ubiquitination of NLRP3 (Yen et al, 2015), and LPS along with ATP stimulation initiated K63‐ and K48‐linked polyubiquitination of NLRP3 (J. Tang et al, 2020; Zhang et al, 2022). In the present study, we found that increased K48‐linked polyubiquitination of NLRP3 was observed upon downregulating USP9X.…”
Section: Discussionmentioning
confidence: 99%
“…Among many epigenetic modifications studied, the m 6 A modification in RNA has been proven to play an important role in the development and treatment of sepsis. However, the specific function of m 6 A “reading” protein in SIC inflammatory reaction is unclear and whether m 6 A is involved in this process remains unknown (14,41–43). In this study, the m 6 A reader, YTHDC1, was found to increase after LPS stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in the development of pharmacological targeting of ubiquitination and deubiquitination have uncovered a great potential for treatments of cancer, neurodegenerative disorders, inflammatory disorders, immunological diseases and microbial infection [ 30 ]. YTH N6-methyladenosine (m6A) RNA-binding protein 1 (YTHDF1), a reader of m6A, alleviates cecal ligation and perforation-induced sepsis through promoting NLRP3 ubiquitination [ 31 ]. Tranilast blunts NLRP3 inflammasome assembly via enhancing NLRP3 ubiquitination, contributing to the amelioration of vascular inflammation and atherosclerosis [ 32 ].…”
Section: Regulation Of Ubiquitination and Deubiquitination In Nlrp3 I...mentioning
confidence: 99%